Do Non-Executive Employees Matter in Curbing Corporate Financial Fraud - Wu, F.; Cao, June; Zhang, X. (Elsevier, 2023)
Exploiting staggered enactment of employee stock ownership plans (ESOPs) as a quasi-natural shock, we use a difference-in-differences (DiD) approach to investigate whether and how ESOPs mitigate corporate financial fraud in China. We find ESOPs significantly reduce corporate financial fraud. This is because of stock ownership of non-executives rather than executives. The underlying mechanisms are heightened internal monitoring and external monitoring through which ESOPs curb executives’ opportunistic behaviour. Our results are robust to parallel trend test, placebo test, PSM approach, instrument variable test, and considering omitted variable concern, partial observability problem, model specification, stock market crash, and industry effect. Our additional analyses indicate that the effect of ESOPs on corporate financial fraud is more pronounced when firms with weaker corporate governance, poorer information environment, less powerful executives and higher-intensity and broader-based plans. Collectively, our results indicate that ESOPs play a role, as an alternative corporate governance mechanism, in mitigating financial fraud.